Numerical and experimental investigation of texture shape and position in the macroscopic contact. (June 2018) - Codrignani, A.; Frohnapfel, B.; Magagnato, F.; Schreiber, P.; Schneider, J.; Gumbsch, P.
Abstract: In this work, the influence of operating conditions on the shape parameters of surface texture is investigated by means of both numerical and experimental investigations. The analysed texture consists of micro-dimples obtained through laser surface texturing on a pin-on-disc configuration. From the numerical point of view, particular attention is paid to the faithful representation of the 2D surface of the experimental set-up and to modelling cavitation phenomena through a mass conserving algorithm. As results, the dimple depth shows a higher relevance than diameter in determining the optimal texture shape (both in terms of friction reduction and load carrying capacity). Moreover, the dimple depth, corresponding to the minimal friction, is found to scale with the square root of the Sommerfeld number in agreement with the experimental results. Finally, it is found that a numerical approach with the present hydrodynamic model cannot account for friction reduction obtained experimentally with different orientation of the texture.